GAGASAN TAFSIR MAQASHIDI: SEJARAH, TEORI DAN APLIKASINYA - Mahmud, Rijal (Universitas Islam Negeri Mataram, 2017)
One of the problematic issues in the context of democracy and human rights issue is talking about punishing riddah (musrik people became believers and believers become musrik again). Interpretation against the Quran as a primary source and guiding Muslims needed to solve the problem of riddah this, one of which can be solved by an approach trends of al-Sharia, better known as Tafsir maqashidi. Maqasid alShariah in General can be interpreted with the aim of legislation to achieve the benefit and prevents kemudaratan. Problems of riddah, the clerics ‘ interpretation of it can be examined by applying the theory of maqasid al-Shariah in understanding the riddah case by noticing how the context when the verse and Hadith that appear can be acquired new meaning, so it is able to give answers to problems that occur and in accordance with the context of the present.